2020
DOI: 10.1212/wnl.0000000000010576
|View full text |Cite
|
Sign up to set email alerts
|

Late seizures in cerebral venous thrombosis

Abstract: Objective:To examine the incidence, characteristics, treatment, and predictors of late seizures (LS) after cerebral venous thrombosis (CVT), we described these features in a registry of 1,127 patients with CVT.Methods:We included consecutive adult patients from an international consortium of twelve hospital-based CVT registries. We excluded patients with a history of epilepsy or with <8 days of follow-up. We defined LS as seizures occurring >7 days after diagnosis of CVT. We used multivariable Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 28 publications
(31 reference statements)
4
27
0
2
Order By: Relevance
“…Post‐vaccination CVST cases were additionally compared to a control group of CVST patients diagnosed prior to the COVID‐19 pandemic. Data for this control sample were derived from the International CVST Consortium, which is an academic collaboration established in 2015 with the aim of performing clinical research on CVST [11–14]. CVST patients from three participating European hospitals (Table S4) with symptom onset between 1 January 2015 and 31 December 2017 were used as a control sample.…”
Section: Methodsmentioning
confidence: 99%
“…Post‐vaccination CVST cases were additionally compared to a control group of CVST patients diagnosed prior to the COVID‐19 pandemic. Data for this control sample were derived from the International CVST Consortium, which is an academic collaboration established in 2015 with the aim of performing clinical research on CVST [11–14]. CVST patients from three participating European hospitals (Table S4) with symptom onset between 1 January 2015 and 31 December 2017 were used as a control sample.…”
Section: Methodsmentioning
confidence: 99%
“…Cumulative incidence of recurrence ranges between 18% and 73% in mixed stroke cohorts after variable follow‐up, 42%‐81% in ischemic stroke cohorts, and 28%‐84% in ICH. 2 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Long‐term survival‐adjusted risks (3‐10 years) have been reported at >70% for mixed and ischemic stroke populations (Table 2 ). One study reported 70% CI of recurrence after a remote seizure in central venous thrombosis.…”
Section: Strokementioning
confidence: 99%
“…45 Late seizures occur in 11% of patients, especially in patients with intracranial bleeding, acute symptomatic seizures, or who underwent decompressive hemicraniectomy. 46…”
Section: Treatmentmentioning
confidence: 99%